Hadid suresinin eğitim açısından yorumu - Arslan, Z. Şeyma (My University, 1999)
OF THE THESIS Our thesis with the topic The Commentary of Suretul Hadid on Education consists of a Foreword, an Introduction,two Main Topics and a Conclusion. The Main idea of this work is to examine the Quran from the perspektive of education, and to detect some facts which will clarify our educational activities. The Foreword is based on this fact. Yn the introduction, topic choise and reason, research style and plan are defined, and about Suretul Hadid is presented. After this introduction part, the explanation of the topics in this Sure fallows. In the first part, the problem of Hypocracy, Yslam's point of Earth and Afterworld lives with fate topic, and the answer to questle of wath Allah is, are presented in the same faith part of the Sure. In the second part, topics about prayers are presented in the same sequence on they appear through it. In this part with the name Prayers and Education, Tesbih prayers, Ynfak prayers, reverence concept and moral education, justice and education, Holy Books' Believers and clergy are detailed. In each part, first the original written and measing of the ayets in Suretul Hadid, to be innformed are given. Then -to understand and clarify the right meanity of these ayets - a short reference to Mufessirs explanations are added. And lastly other linked ayet in the Quran are presented. As a conclusion to all, subjects an education are given. The main point of Suretul Hadid is to put faith in humans soul and trough this faith to reach the reasoning of bewary of Allah, reverence, self sacrifice, temperance and sincerity. TEZ ÖZETY Hadid Suresi'nin E?itim Açysyndan Yorumu adly tezimiz önsöz, giri?, iki ana bölüm ve sonuçtan olu?maktadyr. Bu çaly?manyn dayandy?y temel dü?ünce Kur'an'a e?itim perspektifinden bakmak ve e?itim faaliyetimizde bize yol gösterecek bazy hususlary tesbit etmektir. Çaly?manyn önsözünde bu temel dü?ünce üzerinde durulmu?tur. Giri? bölümünde konu seçimi ve amacy, ara?tyrmanyn yöntemi, ara?tyrmanyn plany hakkynda bilgi verilip, Hadid Suresi hakkynda yklanmy?tyr. Bu giri? bölümünden sonra Surede ele alynan konularyn açyklamasyna geçilmi?tir. Birinci bölümde Allah'yn tanytylmasy, münafyklyk meselesi ve Yslam'yn dünya-ahiret hayaty ve kader mevzuuna baky?y konulary ele alynmy?tyr. Bunlar Surede geçen iman alanyyla alakaly konular oldu?undan, bir ba?lyk altynda toplanmy?tyr. Ykinci bölümde ise ibadet sahasyyla alakaly görülen konular Surede geçtikleri syra ile ele alynmy?tyr. Ybadet ve E?itim ba?ly?y altynda bu bölümde tesbih ibadeti, infak ibadeti, hu?u kavramy ve kalp e?itimi, adalet ilkesi ve e?itim, ehl-i kitap ve ruhbanlyk mevzulary ele alynmy?tyr. Her bir bölümde önce Hadid Suresinin o bölümde ele alynacak olan ayetlerinin metin ve mealleri verilmi?, daha sonra bu ayetleri do?ru anlamak ve de?erlendirmek için müfessirlerin açyklamalary kysaca zikredilmi? ve Kur'an-y Kerim'de ayny konuyla alakaly di?er ayetlere de atyflarda bulunulmu?tur. Bütün bunlaryn neticesinde e?itimle ilgili hususlara geçilmi?tir. Ele aldy?ymyz Hadid Suresinin üzerinde dönüp dola?ty?y ana nokta imany kalplerde yerle?tirmek ve bu imandan ne?et eden takva, hu?u, samimiyet, fedakarlyk ve itidalli olma haline ula?maktyr.
Keywords: Ayetler ve sureler (Kuran); Din; İslam Dini